2016
DOI: 10.1016/j.jtrangeo.2016.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of car ownership among young households in the Netherlands: The role of urbanisation and demographic and economic characteristics

Abstract: Determinants of car ownership among young households in the Netherlands General rightsIt is not permitted to download or to forward/distribute the text or part of it without the consent of the author(s) and/or copyright holder(s), other than for strictly personal, individual use, unless the work is under an open content license (like Creative Commons). Disclaimer/Complaints regulationsIf you believe that digital publication of certain material infringes any of your rights or (privacy) interests, please let the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
37
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(53 citation statements)
references
References 23 publications
2
37
0
3
Order By: Relevance
“…Researchers in other countries have found that important factors for car ownership include individual and household income, employment status, household location, cultural background, car price, energy prices, access to public transportation, build environment, etc. [13][14][15][16]. Thus, more research is needed to explore such factors in China.…”
Section: Background Literaturementioning
confidence: 99%
“…Researchers in other countries have found that important factors for car ownership include individual and household income, employment status, household location, cultural background, car price, energy prices, access to public transportation, build environment, etc. [13][14][15][16]. Thus, more research is needed to explore such factors in China.…”
Section: Background Literaturementioning
confidence: 99%
“…According to previous studies, there are five main categories of determinants that positively or negatively affect household car ownership levels (8,(12)(13)(14). First, traditional economic factors, including household income, vehicle prices, and fuel costs affect household car ownership levels (2,8,13,(15)(16)(17)(18)(19).…”
Section: Modeling Household Car Ownership Background Literature On Homentioning
confidence: 99%
“…First, traditional economic factors, including household income, vehicle prices, and fuel costs affect household car ownership levels (2,8,13,(15)(16)(17)(18)(19). For example, higher income levels positively affect car ownership levels, whereas lower levels of income, in a limited way, affect car ownership levels (15).…”
Section: Modeling Household Car Ownership Background Literature On Homentioning
confidence: 99%
See 2 more Smart Citations